2020
DOI: 10.24014/jdr.v31i2.10874
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Legitimasi Zakat Profesi Dari Dimensi Syariah Dan Regulasi Di Indonesia

Abstract: The total potential for zakat profession is IDR. 139.07 trillion, or 59.5 percent of Rp's total national zakat potential. 233.8 trillion. Meanwhile, the realization only reached IDR. 3.9 trillion or 2.8%. This study aims to analyze the zakat profession from the sharia and regulatory dimensions. This study uses a qualitative method with a descriptive approach and literature study. The research data was obtained by collecting and reviewing previous research results that were relevant to the theme. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…37 The technology referred to here is not creating technology but utilizing and optimizing existing technology services to convey da'wah messages by filling programs with Islamic nuances, visual and audio, or live streaming. 38 In addition, it involves using technology such as applications, websites, and other digital platforms to spread da'wah messages to the public. 39 Through this approach, it is necessary to consider the use of appropriate and accessible technology by the community to convey the da'wah message effectively.…”
Section: Technology-based Approachmentioning
confidence: 99%
“…37 The technology referred to here is not creating technology but utilizing and optimizing existing technology services to convey da'wah messages by filling programs with Islamic nuances, visual and audio, or live streaming. 38 In addition, it involves using technology such as applications, websites, and other digital platforms to spread da'wah messages to the public. 39 Through this approach, it is necessary to consider the use of appropriate and accessible technology by the community to convey the da'wah message effectively.…”
Section: Technology-based Approachmentioning
confidence: 99%
“…In Indonesia, zakat management is carried out by zakat management entities consisting of Baznas, Baznas Province branch, Baznas District/City branch, and LAZ. Bahri et al (2020) identified 572 zakat management entities in Indonesia (Baznas, 2020b). Several studies, e.g.…”
Section: Literature Review Zakat Managementmentioning
confidence: 99%
“…This model is seen as realising good organisational governance with three principles: trustworthy, transparent, and professional (Bahri, 2013). Therefore, zakat management is regulated in regulations at the macro, meso, and micro levels (Bahri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengan demikian, pengumpulan zakat di Indonesia, mempunyai dasar yang kuat yaitu: syariat dan regulasi. Ini didukung oleh beberapa peneliti antara lain: Bahri et al (2020), Marimin & Fitria (2015) dan Mth (2007).…”
Section: Pendahuluanunclassified